Nitrogen donor ligand for capping ZnS quantum dots: a quantum chemical and toxicological insight. Issue 49 (11th September 2019) - Pandey, Vivek; Tripathi, Vinay Kumar; Singh, Keshav Kumar; Bhatia, Tejasvi; Upadhyay, Nitesh Kumar; Goyal, Bela; Pandey, Gajanan; Hwang, Inho; Tandon, Poonam
Abstract : Nanoparticles having strong optical and electronic properties are the most widely used materials in sensor development. Abstract : Nanoparticles having strong optical and electronic properties are the most widely used materials in sensor development. Since the target analyte interacts directly with the surface of the material, the choice of ligand for functionalizing the surface of the material is the key for its further applications. The functionalized surface of the material makes it suitable for required applications as it controls the size of the particle during its growth from the solution phase. Biomolecule capped nanomaterials are favourable for various applications in bio-sensing. In the present work, an attempt has been made to explore the biologically active molecule imidazole as capping agent for ZnS semiconductor nanoparticles or quantum dots (QDs). This work explores the possibility of replacing conventional thiol-zinc bonding and hence paves new pathways for biomolecules having the possibility of being efficient capping agents. Computational chemistry has been used to study the mechanism of bonding between one of the nitrogen atoms of imidazole and the zinc ion of the ZnS QDs. The quantum chemical insight not only explores the most spontaneous interaction of zinc ion and imidazole molecule so as to act as an efficient capping agent but also explains the probable bonding site for nitrogen–zinc chemistry. The tailormade Mn doped ZnS QDs are one of the most promising materials for probe and sensor development. The ZnS core having non-toxicity and the emission in longer wavelength due to manganese makes this material highly useful biologically. The aqueous route of synthesis has been employed to obtain a highly homogeneous and pure material which was further characterized by UV (Ultra Violet spectroscopy), Spectrofluorometer, Transmission Electron Microscope and X-ray Diffraction. The toxicity at the cellular and genetic levels was also investigated to prove the potential of the imidazole capped Mn doped ZnS QD as a biocompatible material.